Cyanoacrylate adhesive versus fast-absorbing gut suture for cutaneous closure in upper blepharoplasty: a systematic review - Householder, Nicholas; Ray, Coby (Aesthetic Medicine, 2025)
Background: the choice of suture material for upper blepharoplasty remains highly variable and is often influenced by individual surgeon preferences. Absorbable sutures and cyanoacrylate adhesives offer distinct advantages due to their biodegrading ability, namely increased patient comfort and convenience. However, the current literature lacks direct comparative studies on these materials, and questions persist regarding their strength, durability, and wound-healing characteristics. Aim: this review assesses the functional and cosmetic effectiveness of absorbable sutures and cyanoacrylate for cutaneous closure in upper blepharoplasty. Methods: the review focuses on studies published since 2000 that compare absorbable sutures and cyanoacrylate use in upper blepharoplasty. A systematic search was conducted using several databases. Inclusion criteria encompassed clinical trials or case series assessing cutaneous closure in upper blepharoplasties. Results: five studies met the inclusion criteria and presented various outcomes. In some cases, cyanoacrylate closure demonstrated the potential for superior cosmetic results and reduced closure time. However, a closure with gut sutures alone tended to show a higher dehiscence risk than non-absorbable sutures, though cosmetic results may have been equivalent. No papers were found evaluating synthetic absorbable sutures. Conclusion: the included studies were limited by their design, small sample sizes, and limited follow-up durations. The lack of objective measures in the assessment of cosmetic outcomes made it challenging to form direct cross-comparisons. In summary, while absorbable gut suture and cyanoacrylate present satisfactory results in upper blepharoplasty closure, cyanoacrylate primary closure may provide enhanced cosmesis in addition to inherent practical advantages. Surgeons may consider these alternatives over non-absorbable sutures, considering their resource-saving potential and patients’ comfort.